Effects of Nonaqueous Phase Liquids Pollution on the Permeability and Microstructure of In-Filed and Laboratory Soaked Contaminated Clay Soils - Yanbin Gao; Jiadan Liu (Geofluids)
The fact that the permeability and microstructure properties of clay will be changed by NAPL (Nonaqueous Phase Liquids) pollution draws high attention in the study of the interaction between NAPL and contaminated soil. Through in-field contaminated clay soils from vinyl chloride and 1, 1, 2-trichloroethane-contaminated site in Shanghai, the variation of the content of vinyl chloride and 1, 1, 2-trichloroethane pollutants in clay with depth was obtained. The change of plasticity, permeability, and microstructure properties of the clay samples contaminated by vinyl chloride and 1, 1, 2-trichloroethane were investigated in detail. The measured test results were compared with the uncontaminated clay and indoor soaked contaminated clay samples by TCE (Trichloroethylene). The test results showed that the microstructure characteristics of clay were changed under the influence of the content of TCE, vinyl chloride, and 1, 1, 2-trichloroethane. The total porosity, accumulative pore volume, and the content of the macroporosity percentage of clay soils showed an increasing trend. The flocculation structure of contaminated clay samples was observed, but there were no overhead pores and connected cracks. Volatile organic pollutants were detected in both field and indoor contaminated clay samples. The plastic limit and liquid limit of each layer of contaminated samples decreased slightly, the plastic index did not change significantly, and the pore ratio and permeability coefficient increased gently. At the same time, the clay shrinkage was aggravated by TCE pollution, and cracks appeared on the surface of soil samples. However, no connected cracks were formed. Test results indicated that the self-developed improved permeability test device can be used to test the permeability coefficient of clay samples with shrinkage and to crack by NAPL pollution. The permeability coefficient showed an increasing trend, though the increase was not at the level of magnitude.